High-intensity interval training (HIIT) for patients with chronic diseases - Leanna M. Ross; Ryan R. Porter; J. Larry Durstine (Elsevier, 2016)
Exercise training provides physiological benefits for both improving athletic performance and maintaining good health. Different exercise training modalities and strategies exist. Two common exercise strategies are high-intensity interval training (HIIT) and moderate-intensity continuous exercise training (MCT). HIIT was first used early in the 20th century and popularized later that century for improving performance of Olympic athletes. The primary premise underlying HIIT is that, compared to energy expenditure-matched MCT, a greater amount of work is performed at a higher intensity during a single exercise session which is achieved by alternating high-intensity exercise intervals with low-intensity exercise or rest intervals. Emerging research suggests that this same training method can provide beneficial effects for patients with a chronic disease and should be included in the comprehensive medical management plan. Accordingly, a major consideration in developing an individual exercise prescription for a patient with a chronic disease is the selection of an appropriate exercise strategy. In order to maximize exercise training benefits, this strategy should be tailored to the individual's need. The focus of this paper is to provide a brief summary of the current literature regarding the use of HIIT to enhance the functional capacity of individuals with cardiovascular, pulmonary, and diabetes diseases.